ESR spectroscopy as a new method to analyze the synergy between two different nanofillers dispersed in an elastomer matrix. (February 2019) - Ivanoska-Dacikj, Aleksandra; Bogoeva-Gaceva, Gordana; Valić, Srećko
Abstract: In this study electron spin resonance (ESR) investigations on hybrid natural rubber based nanocomposites loaded with 2 phr of multi-walled carbon nanotubes (MWCNT) and various concentrations of expanded organically modified montmorillonite (EOMt) (0; 8 and 16 phr) were reported. The temperature dependence of the resonance line parameters in the range 160–353 K was analyzed. From the obtained results it was evident that the presence of the EOMt influences the appearance of the ESR spectra. This influence makes it possible to assess the state of dispersion of the hybrid nanofiller in the rubber matrix only by analyzing the line shape of the resonance ESR spectra. The Lorenzian line shape indicates good dispersion of the nanofillers while Dysonin line shape suggests re-agglomeration. The increase of the g -factor, or resonance line position values, when EOMt is present in the matrix suggests that the EOMt and MWCNT interact in such a way that the content of the defects in the multi-walled carbon nanotubes decreases. Highlights: The ESR spectra of the hybrid NR based nanocomposite was measured over the temperature range 160–353 K. The presence of the EOMt influences the appearance of the ESR spectra. ESR spectroscopy can be successfully applied for analysis of complex interactions appearing between different nanofillers. EOMt and MWCNT interact in such a way that the content of the defects in the MWCNT decreases. ESR spectroscopy could be used to assess the state of dispersion of the hybrid nanofiller.